Rat heart: A site of oxytocin production and action - Jankowski, Marek (The National Academy of Sciences, 1998)
We report here that the rat heart is a site of oxytocin (OT) synthesis and release. Oxytocin was detected in all four chambers of the heart. The highest OT concentration was in the right atrium (2128 ± 114 pg/mg protein), which was 19-fold higher than in rat uterus but 3.3-fold lower than in the hypothalamus. OT concentrations were significantly greater in the right and left atria than in the corresponding ventricles. Furthermore, OT was released into the effluent of isolated, perfused rat heart (34.5 ± 4.7 pg/min) and into the medium of cultured atrial myocytes. Reverse-phase HPLC purification of the heart extracts and heart perfusates revealed a main peak identical with the retention time of synthetic OT. Southern blots of reverse transcription–PCR products from rat heart revealed gene expression of specific OT mRNA. OT immunostaining likewise was found in atrial myocytes and fibroblasts, and the intensity of positive stains from OT receptors paralleled the atrial natriuretic peptide stores. Our findings suggest that heart OT is structurally identical, and therefore derived from, the same gene as the OT that is primarily found in the hypothalamus. Thus, the heart synthesizes and processes a biologically active form of OT. The presence of OT and OT receptor in all of the heart’s chambers suggests an autocrine and/or paracrine role for the peptide. Our finding of abundant OT receptor in atrial myocytes supports our hypothesis that OT, directly and/or via atrial natriuretic peptide release, can regulate the force of cardiac contraction.